Lucio V. Mansilla, a man of letters? (Anclajes, 2019)
This work proposes to map a set of texts that outline the evasive and complex literary identity of Lucio V. Mansilla. Pivoting around the image of the conversationalist, Mansilla can bend to the idea of a writer measured at times with the figure of the man of letters but, at other times, with that of the critic (both invested with authority in the 1980s), and nurtured, in turn, by that of the cultural journalist (figure around which decisive transformations are processed in the social identity of the writer in Argentina in order century). Our hypothesis is that this construction could be seen as an episode -informal and heterodox, like all those starring by Mansilla- of the emerging literary life in the last decades of 19th century in Argentina.
Keywords: Lucio V. Mansilla; man of letters; literary criticism; journalism; 80´s decade